2021
DOI: 10.5664/jcsm.8860
|View full text |Cite
|
Sign up to set email alerts
|

A population-based estimate of the health care burden of obstructive sleep apnea using a STOP-BAG questionnaire in South Carolina

Abstract: Study Objectives: Population based estimates of obstructive sleep apnea (OSA) frequency and health impact are incomplete. The aim of this study was to determine the prevalence of risk factors for physician and sleep study diagnosed OSA among individuals in a state-based surveillance program Methods: Using questions inserted into the 2016 (n = 5,564) and 2017 (n = 10,884) South Carolina Behavioral Risk Factor Surveillance System of the Centers for Disease Control and Prevention, we analyzed the prevalence of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
4
2
0
Order By: Relevance
“…Additionally, the prevalence of high risk, defined by STOP-BAG scores of 5 or higher, was found to be 15.2% of the population. This finding aligns with a previous United States study [ 23 ] that acknowledged the difficulty in determining the prevalence of undiagnosed individuals in the population. Moreover, the study revealed that 44% of the population, as identified by the STOP-BANG score while the current diagnosis rate was only 10% and these results underscore the magnitude of the public health crisis, representing a significant and urgent issue of epidemic proportions [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the prevalence of high risk, defined by STOP-BAG scores of 5 or higher, was found to be 15.2% of the population. This finding aligns with a previous United States study [ 23 ] that acknowledged the difficulty in determining the prevalence of undiagnosed individuals in the population. Moreover, the study revealed that 44% of the population, as identified by the STOP-BANG score while the current diagnosis rate was only 10% and these results underscore the magnitude of the public health crisis, representing a significant and urgent issue of epidemic proportions [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…This finding aligns with a previous United States study [ 23 ] that acknowledged the difficulty in determining the prevalence of undiagnosed individuals in the population. Moreover, the study revealed that 44% of the population, as identified by the STOP-BANG score while the current diagnosis rate was only 10% and these results underscore the magnitude of the public health crisis, representing a significant and urgent issue of epidemic proportions [ 23 ]. Our previous study demonstrated a positive association between higher scores on the STOP-BAG instrument and an increased risk of multimorbidity [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, unlike the elderly, middle-aged people, who are at high risk of OSA, often have stressful and suicidal thoughts. These findings are consistent with those of previous studies [33][34][35]. However, these studies did not analyze middle-aged and adults separately; hence, further research is required.…”
Section: Discussionsupporting
confidence: 91%
“…In the US population, men who snore or stop breathing more than 5 nights/week have the strongest association with probable major depression [ 27 ]. A previous study showed that a high OSA risk determined by the STOP-BANG questionnaire was more often diagnosed with depression than with low risk for 16,448 in South Carolina, United States [ 26 ]. Psychological stress was high in patients with OSA, and the presence of OSA, not severity, and was related to depression and anxiety in 44 untreated participants with OSA and 57 health controls in a study in the United States [ 28 ].…”
Section: Discussionmentioning
confidence: 99%